ANALISIS PEMAHAMAN KONSEP PESERTA DIDIK DITINJAU DARI KEMAMPUAN METAKOGNISI PESERTA DIDIK PADA MATERI BILANGAN PECAHAN - Khoiruddin, Muadz; Vahlia, Ira; Rahmawati ES, Yeni (EMTEKA: Jurnal Pendidikan Matematika, 2024)
Students claim to be quite difficult to understand the concept of faroidh fractional numbers, therefore it is necessary to carry out more in-depth research related to the ability to understand the concepts of students. The purpose of this study is to describe the understanding of students' concepts based on metacognition abilities on faroidh fractional number material carried out at MA Al Muhsin Metro. This type of research is qualitative research. In this study, subjects were obtained using the purposive sampling method. The subjects used were 6 students. The instruments used are questionnaires, questions and interviews. The results of this study showed that subjects with high metacognition abilities were able to meet all indicators of concept understanding. Subjects with moderate metacognition abilities did not meet all indicators of concept understanding on some questions. Subjects with low metacognition abilities are unable to meet the indicators of concept understanding, namely developing necessary conditions and applying problem-solving concepts.